Implementation of Ethnoscience-Based Learning in The Manifestation of Character Education in Elementary Schools - Lestari, Nyoman Ayu Putri (Universitas Muhammadiyah Surakarta, 2023)
The lack of effective learning strategies in fostering character education in elementary schools provides a basis for analyzing the implementation of ethnoscience-based learning in the manifestation of character education in Indonesia. This research aimed at the implementation of ethnoscience-based learning in addressing this issue. The research method employed is a literature review involving the analysis and synthesis of various relevant sources. The findings of this research indicate that the implementation of ethnoscience-based learning can be an effective learning strategy for achieving character education in elementary schools. Ethnoscience-based learning creates a learning environment and designs learning experiences that integrate culture as part of the learning process in elementary schools. The results reveal that through ethnoscience-based learning, students can enhance empathy, develop cultural appreciation, and build environmental awareness. In addition, students also demonstrate a better understanding of cultural diversity and traditions. Thus, this research underscores the importance of implementing ethnoscience-based learning as an effective strategy for realizing character education in elementary schools. Given the challenges faced by the system today, this strategy can serve as a solution to shaping students with character, environmental concern, and cultural appreciation. The findings of this research have significant implications for curriculum development, education policy formulation, and the implementation of learning at the elementary school level.